STRATEGY FOR A HEALTHY LIFESTYLE IS THE PHYSICAL EDUCATION AND HEALTH ACTIVITIES - Sharipova, Gulnara; Makarova, Yelena; Kramorov, Viktor (SWorldJournal, 2024)
The purpose of this article is to consider physical education and sports as a component of a healthy lifestyle. Within the framework of this goal, the following specific tasks are solved: 1. Consideration of the issue of a healthy lifestyle, define the ph